Influence of postharvest treatments and storage conditions on the quality of Hass avocados. Issue 6 (June 2020) - Kassim, Alaika; Workneh, Tilahun Seyoum
Abstract: The purpose of this study was to investigate the influence of postharvest treatments on the shelf life of avocado. The experimental design consists of pre-packaging (hot water and wax), packaging (low-density polyethylene and biodegradable films), and storage temperatures (ambient and cold storage), which was arranged in a randomized complete block design with three replications. The effects of combined postharvest treatments on the changes in the physical, chemical, and sensory quality of 'Hass' avocados during a 28-day cold chain simulation were evaluated. The quality parameters evaluated included puree viscosity, moisture content, dry matter, pH, total soluble solids, total titratable acid and subjective quality attributes. Storage conditions significantly (P ≤ 0.05) affected the measured parameters. Cold chain conditions (5.5 °C for two days, 5 °C for six days and 4.5 °C for 20 days at 95% relative humidity) offered the most significant benefit in maintaining higher fruit quality. The combination of a wax coating, low-density polyethylene packaging, and cold chain conditions was beneficial in delaying ripening by approximately two weeks with minimum changes in moisture content (9.5%) and TSS (19.0%) and viscosity. Cold storage is essential in improving the shelf life and maintaining the quality of avocado fruits during export. Abstract : Food science; Food technology; Avocado; Pre-packaging; Packaging; Cold chain; Storage; Wax; Hot water; Low density polyethylene; Corn starch Biodegradable